Evaluasi Program Kartu Indonesia Sehat (KIS) di Kelurahan Lebung Gajah Kecamatan Sematang Borang Kota Palembang - Islamy, Diah Putri; Hakim, Arif Rahman; Sutinah, Sutinah (@-Publik: Jurnal Administrasi Publik, 2024)
This research aims to determine the evaluation of the Healthy Indonesia Card (KIS) Program in Lebung Gajah Village, Sematang Borang District, Palembang City. This research method is descriptive qualitative where the data collection technique is triangulation, namely interview, observation and documentation techniques. The research results show that the evaluation of the Healthy Indonesia Card (KIS) program has been carried out well, although a small number of them experienced problems. Regarding effectiveness, it can be concluded that the public is satisfied with the kis program in terms of health services and the implementation of kis card distribution is optimal. Efficiency can be concluded that the time to complete the kis making can be categorized as not optimal. Adequacy, it can be concluded that meeting community needs and the available health services are good. Alignment, it can be concluded that equalization is correct. Responsiveness, it can be concluded that the community's response has been right on target. However, there are a small number who do not receive kis, because there are people who do not meet the requirements, especially where they live. Accuracy, it can be concluded that it is in accordance with the objectives and benefits of the kis program that the community needs, namely ensuring the health of the less fortunate with free treatment. In this case, with the kis program, people receive completely free treatment from the government, which means that poor people do not need to think about the costs of treatment at hospitals or health centers.